The Effect of Treatment Education Techniques on Medication Adherence in Tuberculosis Patients at Dr.H Aloei Saboe Hospital - Vivri Yanti Van Gobel; Fadli Syamsuddin; Haslinda Damansyah (Universitas Muhammadiyah Palu, 2026)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis and is one of the leading causes of death worldwide. In Indonesia, the number of TB cases is quite high, and patient adherence to taking medication is very important for the control of this disease. The purpose of this study is to find out whether there is an influence of educational techniques on patient adherence in taking anti-tuberculosis drugs. The design of this study uses a quasi-experimental design with a one group pretest-posttest approach. The sample consisted of 17 respondents, Data was collected through questionnaires before and after educational interventions using video media.data analysis using the wilcoxon test p<0.05. Results Before the intervention, only 5.9% of respondents showed adherence in taking medication. After the educational intervention, the compliance rate increased to 82.4%. The Wilcoxon test showed a p< value of 0.05, which indicates a significant difference between pre- and post-education compliance. This shows that educational techniques effectively increase patients' understanding of the importance of taking medication regularly Conclusion There is a significant influence of educational techniques on medication adherence in tuberculosis patients at Prof. Dr. H. Aloei Saboe Hospital. This research shows that effective education can increase patient adherence to treatment, which contributes to a faster healing process.